Hybrid character of a large neurofilament protein (NF-M): intermediate filament type sequence followed by a long and acidic carboxy-terminal extension. - Geisler, N (1984)
The sequence of the amino-terminal 436 residues of porcine neurofilament component NF-M (apparent mol. wt. in gel electrophoresis 160 kd), one of the two high mol. wt. components of mammalian neurofilaments, reveals the typical structural organization of an intermediate filament (IF) protein of the non-epithelial type. A non-alpha-helical arginine-rich headpiece with multiple beta-turns (residues 1-98) precedes a highly alpha-helical rod domain able to form double-stranded coiled-coils (residues 99-412) and a non-alpha-helical tailpiece array starting at residue 413. All extra mass of NF-M forms, as a carboxy-terminal tailpiece extension of approximately 500 residues, an autonomous domain of unique composition. Limited sequence data in the amino-terminal region of this domain document a lysine- and particularly glutamic acid-rich array somewhat reminiscent of the much shorter tailpiece extension of NF-L (apparent mol. wt. 68 kd), the major neurofilament protein. NF-M is therefore a true intermediate filament protein co-polymerized with NF-L via presumptive coiled-coil type interactions and not a peripherally bound associated protein of a filament backbone built exclusively from NF-L. Along the structurally conserved coiled-coil domains the two neurofilament proteins show only approximately 65% sequence identity, a value similar to that seen when NF-L and NF-M are compared with mesenchymal vimentin. The highly charged and acidic tailpiece extensions of all triplet proteins particularly rich in glutamic acid seem unique to the neurofilament type of IFs. They could form extra-filamentous scaffolds suitable for interactions with other neuronal components.(ABSTRACT TRUNCATED AT 250 WORDS)